Peningkatan Pemahaman dan Keterampilan Konselor dalam Pemanfaatan Teknologi melalui Pelatihan Pemanfaatan Google Sites - Widya Juwita Sari; Ismarini Bekti Setiani; Agus Triyanto (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
One of them is the lack of adequate counselor skills in the use of technology for guidance and counseling services. In the current era, guidance and counseling services are faced with various challenges and opportunities. One of them, counselors must be able to adapt to technological developments. This is a need for the younger generation in the current era as recipients of guidance and counseling services. One use of technology in guidance and counseling is to develop service media via the Google sites. Counselors need to receive training in media development for guidance and counseling services via the Google sites. Google sites provides ease of use and high accessibility so that it will make it easier for counselees to understand and increase students' interest and motivation to participate in guidance and counseling services. The targets of the training were 30 high school guidance and counseling teachers who were members of the Yogyakarta Special Region High School Guidance and Counseling Teachers' Conference. This study uses a qualitative approach by collecting observational data, comprehension tests, and content development results. The results of the training show an increase in the ability of guidance and counseling teachers in developing online guidance and counseling service media using the Google sites.